Does the evidence support brief (≤30-mins), moderate (31–60-mins), or long duration naps (61+ mins) on the night shift? A systematic review. (October 2021) - Patterson, P. Daniel; Liszka, Mary K.; Mcilvaine, Quentin S.; Nong, Lily; Weaver, Matthew D.; Turner, Rose L.; Platt, Thomas E.; Opitz, Samantha E.; Guyette, Francis X.; Martin-Gill, Christian; Weiss, Leonard S.; Buysse, Daniel J.; et al.
Summary: We performed a systematic review of four databases to determine if the evidence supports a short or long duration nap during night shifts to mitigate fatigue, and/or improve health, safety, or performance for emergency services and public safety personnel (PROSPERO CRD42020156780). We focused on experimental research and evaluated the quality of evidence with the grading of recommendations, assessment, development, and evaluation (GRADE) framework. We used the Cochrane Collaboration's risk of bias tool to assess bias and reported findings using the preferred reporting items for systematic reviews and meta-analyses (PRISMA) statement. Our search yielded n = 10, 345 records and n = 44 were reviewed in full-text. Inter-rater agreement during screening was substantial (Kappa = 0.66). We retained n = 11 publications, reporting on n = 7 experimental studies with a cumulative sample size of n = 140. We identified wide variation in study design, napping interventions (i.e., timing, placement, and duration), and outcomes. We identified mixed findings comparing brief, moderate, and long duration naps on outcomes of interest. All seven studies presented serious risk of bias and the quality of evidence was rated as low. Based on the best available evidence, decisions regarding nap duration during night shift work should be based on time (post-nap) and outcome.